Conversion of Reactive Astrocytes to Induced Neurons Enhances Neuronal Repair and Functional Recovery After Ischemic Stroke - Jiang, Michael Qize; Yu, Shan Ping; Wei, Zheng Zachory; Zhong, Weiwei; Cao, Wenyuan; Gu, Xiaohuan; Wu, Anika; McCrary, Myles Randolph; Berglund, Ken; Wei, Ling (Frontiers in Aging Neuroscience, 2021)
The master neuronal transcription factor NeuroD1 is able to directly reprogram astrocytes into induced neurons (iNeurons) after stroke. Using viral vectors to drive ectopic ND1 expression in gliotic astrocytes after brain injury presents an autologous form of cell therapy for neurodegenerative disease. Cultured astrocytes transfected with ND1 exhibited reduced proliferation and adopted neuronal morphology within 2-3 weeks later, expressed neuronal/synaptic markers, and extended processes. Whole-cell recordings detected firing of evoked action potentials in converted iNeurons. Focal ischemic stroke was induced in adult GFAP-Cre-Rosa-YFP mice that then received ND1 lentivirus injections into the peri-infarct region 7 days after stroke. Reprogrammed cells did not express stemness genes, while 2-6 weeks later converted cells were co-labeled with YFP (constitutively activated in astrocytes), mCherry (ND1 infection marker), and NeuN (mature neuronal marker). Approximately 66% of infected cells became NeuN-positive neurons. The majority (~80%) of converted cells expressed the vascular glutamate transporter (vGLUT) of glutamatergic neurons. ND1 treatment reduced astrogliosis, and some iNeurons located/survived inside of the savaged ischemic core. Western blotting detected higher levels of BDNF, FGF and PSD-95 in ND1-treated mice. MultiElectrode Array (MEA) recordings in brain slices revealed that the ND1-induced reprogramming restored interrupted cortical circuits and synaptic plasticity. Furthermore, ND1 treatment significantly improved locomotor, sensorimotor, and psychological functions. Thus, conversion of endogenous astrocytes to neurons represents a plausible, on-site regenerative therapy for stroke.